Evaluating the Expectations of the Elderly from Their Children by Gender in Tehran - Zahra Ali Bakhshi; Shahla Kazmipour Sabet (Iranian Evolutionary Educational Psychology Journal)
Objective: The elderly possess distinctive anticipations from their offspring, shaped by their extensive life experiences and comprehension, in addition to the challenges associated with aging, such as diminished physical capabilities. It is imperative that these anticipations be recognized and addressed, as they may manifest either overtly or covertly. Nonetheless, the identification of the expectations harbored by aging parents concerning their children is crucial. Methods: With regard to practical orientation, employing a deductive-inductive methodology, and classified as quantitative research, the current study was premised on the systematic collection of data from specialists in gerontology, whose statistical population comprised university academics and researchers actively engaged in the field of aging. The statistical sample included twelve individuals, with data gathered separately for elderly females and elderly males. A random sampling technique was employed for the selection process. The acquired data were subsequently analyzed utilizing the Best-Worst Method (BWM), with MATLAB software facilitating the execution of this analytical approach. Results: The analysis revealed a disparity in expectations between male and female elderly individuals regarding their children. Among the male cohort, the paramount anticipations included economic involvement, preservation of assets and property, alongside the imperative of respect. Conversely, for the female elderly population, the foremost expectations encompassed respect, companionship, empathy, a sense of responsibility, aspirations for a prosperous life from their progeny, coupled with the acceptance and reverence of the elderly being of significant importance. Conclusions: The findings elucidated that gender plays a pivotal role in shaping expectations from offspring during the later stages of life, with economic and financial anticipations being predominantly significant for men, whereas relational, emotional, and social expectations hold considerable value for women.